Analisis Pendekatan Pembelajaran Mendalam pada Pembelajaran Membaca Permulaan di SD Negeri Balirejo - Daryanti Apriani; Siti Rochmiyati; Vinalia Gusti Shelawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research is motivated by a question about the deep learning approach that is being intensified by the current ministry of education and how to apply it in the learning process in the field. This research aims to provide a real picture that the application of a deep learning approach can be a solution in solving learning problems. The learning problem in the analysis of the deep learning approach this time is the initial reading ability of grade I students at SD Negeri Balirejo, Yogyakarta City, which is indicated to be still low. The learning methods used in this deep learning approach are storytelling, games, assignments, and individual mentoring in grade I of elementary school. The research method uses qualitative descriptive and descriptive statistical analysis to provide a comprehensive picture of how the learning process in the classroom and the results obtained. The results obtained from this study are that the deep learning approach has been carried out by teachers in early reading learning and can improve early reading skills. This result is seen from the percentage of students who are fluent in reading at the beginning is 23% of the number of students or in the low category, increasing to 82% of the number of students. The conclusion obtained is that the application of an in-depth learning approach can improve the initial reading skills of grade 1 students at Balirejo State Elementary School.